2015
DOI: 10.1016/j.cell.2015.02.046
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of the Human Immune System: A Bioresource for Autoimmunity and Disease Pathogenesis

Abstract: Summary Despite recent discoveries of genetic variants associated with autoimmunity and infection, genetic control of the human immune system during homeostasis is poorly understood. We undertook a comprehensive immunophenotyping approach, analysing 78,000 immune traits in 669 female twins. From the top 151 heritable traits (up to 96% heritable), we used replicated GWAS to obtain 297 SNP associations at 11 genetic loci explaining up to 36% of the variation of 19 traits. We found multiple associations with cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
334
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(346 citation statements)
references
References 62 publications
11
334
1
Order By: Relevance
“…We analyzed human immune cell frequency data from multiple cohorts, described in further detail in Materials and Methods. These are referred to as the Stanford cohorts of 398 individuals, 226 MZ and dizygotic (DZ) twins from a published twin study (4), 23 individuals from a published longitudinal study (11), and 149 previously unpublished subjects (combined in Dataset S1); the Roederer et al (10) cohort, consisting of 669 female twins sampled in the United Kingdom; and the Carr et al (6) cohort, consisting of 670 nontwin subjects, both men and women, sampled in Belgium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed human immune cell frequency data from multiple cohorts, described in further detail in Materials and Methods. These are referred to as the Stanford cohorts of 398 individuals, 226 MZ and dizygotic (DZ) twins from a published twin study (4), 23 individuals from a published longitudinal study (11), and 149 previously unpublished subjects (combined in Dataset S1); the Roederer et al (10) cohort, consisting of 669 female twins sampled in the United Kingdom; and the Carr et al (6) cohort, consisting of 670 nontwin subjects, both men and women, sampled in Belgium.…”
Section: Resultsmentioning
confidence: 99%
“…The PBMCs from the Roederer et al (10) Table S1 for a list of cell subtypes in each cohort), thus precluding a combined clustering analysis of the full dataset. The "monocytes" cell population was removed from the Roederer et al (10) cohort as it was missing in 7.6% of the 729 patients. Of the remaining 32 populations, 11 had missing data in at most 1.6% of patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, gene polymorphisms of ENTPD1 link to the human immune system under homeostatic and inflammatory conditions (e.g. IBD) 9, 10. These lines of evidence suggest that the control of purine metabolism is important in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the HLA class Ⅱ (DRB1*0301) is also associated with chronic HCV infection [33] . Genome-wide association studies of autoimmune disease recently revealed multiple associations with the major immune cell subsets and uncovered insights into the control for regulatory Tregs [34] . AITD clearly increases with age, resulting from changes in immune regulation (endogenous factor).…”
Section: Host-dependent Factors In Thyroid Autoimmunitymentioning
confidence: 99%